PENGARUH KEDISIPLINAN SISWA TERHADAP PRESTASI BELAJAR SISWAKELAS X-IPA SMA NEGERI 15 SEMARANG - Wigati, Sri (Jurnal Karya Pendidikan Matematika, 2019)
Education of the generation of the nation, especially the younger generation, is one of the things that must be considered in order to improve and develop the Indonesian nation. All parties related to the achievement of educational success must cooperate. Starting from the school, parents, government, or the community. One of the successes of education can be seen from learning achievement. In terms of learning, discipline is one of the factors that must be considered. Based on observations made by researchers at Semarang State High School 15, there are still many students who still violate school rules. Therefore, researchers want to know the effect of discipline on student learning outcomes. The research sample was 60 students from 252 students of class X-IPA. The method of data collection is done by using questionnaires and observations. The results of this study indicate that student discipline on student achievement is very influential and it can be seen that the average student discipline is 3.1 which includes the Very Good (SB) category. The Very Good categorized average is directly proportional to student achievement results with an average of 82.